The K+ transporter NPF7.3/NRT1.5 and the proton pump AHA2 contribute to K+ transport in Arabidopsis thaliana under K+ and NO3- deficiency - Sena, Florencia; Kunze, Reinhard (Frontiers in Plant Science, 2023)
Nitrate (NO3 -) and potassium (K + ) are distributed in plants via short and long-distance transport. These two pathways jointly regulate NO3 -and K + levels in all higher plants. The Arabidopsis thaliana transporter NPF7.3/NRT1.5 is responsible for loading NO3 -and K + from root pericycle cells into the xylem vessels, facilitating the long-distance transport of NO3 -and K + to shoots. In this study, we demonstrate a protein-protein interaction of NPF7.3/NRT1.5 with the proton pump AHA2 in the plasma membrane by split ubiquitin and bimolecular complementation assays, and we show that a conserved glycine residue in a transmembrane domain of NPF7.3/NRT1.5 is crucial for the interaction. We demonstrate that AHA2 together with NRT1.5 affects the K + level in shoots, modulates the root architecture, and alters extracellular pH and the plasma membrane potential. We hypothesize that NRT1.5 and AHA2 interaction plays a role in maintaining the pH gradient and membrane potential across the root pericycle cell plasma membrane during K + and/or NO3 -transport.